Assessment of trip experience from Chinese tourists' perspectives on Indonesia tourism - Rahmiati, Filda; Bakri, Mohammed Hariri; Shuyuan, Fu (Editura Universitatii din Oradea, 2021)
With China's rapid economic growth and improved standard of living, travel and tourism are increasingly becoming the first choices for vacation activities. The purpose of this research is to assess the trip experience on destination loyalty through tourist satisfaction of Chinese tourists who visited Indonesia tourism. The quantitative research method was used and the primary data collected using questionnaire to 158 respondents of Chinese tourists who visited Indonesia analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study indicates that 6 of the 7 hypotheses are accepted. As a result, accommodation mediated by tourist satisfaction has no significant effect on destination loyalty. The impact of trip experience on destination loyalty mediated by tourist satisfaction accounted for 64.4 percent. This study demonstrates how Chinese tourists evaluate their trip experiences of Indonesia tourism. Transportation was discovered to have the greatest impact, whereas need to be improved in order to create destination loyalty